A qualitative evaluation of a compassion-focused therapy group intervention for UK healthcare staff at an acute hospital trust - Aikaterini Rammou; Sophie M. Allan; Martha Dean-Tozer; James Baker (PLoS ONE, 2025)
Healthcare staff can encounter empathy distress, burnout, and trauma, often responding with self-criticism rather than self-compassion, yet there remains limited evaluation of compassion-focused interventions for staff with mental health difficulties. This study qualitatively evaluated a compassion-focused therapy (CFT) group intervention offered to National Health System (NHS) staff with mental health difficulties and high self-criticism. A qualitative design using semi-structured interviews was used. Eight staff who attended a 12-week CFT group were interviewed about their experiences learning key CFT concepts, group-based learning, the intervention’s impact on their well-being, and suggestions for improvement. Reflexive thematic analysis was conducted. Participants found the group beneficial, emphasising the development of group safeness, which fostered connection and vulnerability through shared NHS and caregiver identities. CFT content was seen as highly relevant, addressing self-criticism, while helping participants label personal experiences and enhancing self-awareness. The group format fostered a shared understanding of human suffering, reduced feelings of isolation and widened participants’ perspectives through interpersonal learning. Participants reported acquiring skills to support their well-being, with some noting overall emotional improvement. Challenges included emotionally triggering content, highlighting the need for tailored support. Suggestions included smaller group sizes, flexible content delivery to meet individual and group needs, and additional support such as one-on-one sessions or booster sessions. Protected time from work, more information about the group process, and clear expectations were recommended to enhance group safeness and reduce initial hesitation. Group-based CFT was described as acceptable and beneficial, offering preliminary evidence for its potential to support NHS staff with mental health difficulties and pervasive self-criticism. Larger, mixed-method evaluations are recommended to explore the intervention’s broader impact and mechanisms.